Impact of Career Path Strategy on Healthcare Workers' Performance in Government Hospital - Sinaga, Widya Oktaviani; Ginting, Chrismis Novalinda; Siregar, Santy Deasy (Universitas Padjadjaran, 2024)
In the last ten years, the government of Indonesia aggressively built multiple hospitals in the underdeveloped, borders, and islands regions and regions with health problems to tackle the lack of healthcare service in those regions. These hospitals are run by three types of healthcare workers i.e., government employees, contract employees, and honorary employees. Regardless of their type of employment, all healthcare workers are required to adhere to the standard of care and are expected to perform their best at their jobs. However, the different career path among these three types of healthcare workers often impacts their job performance. This study aims to ascertain the impact of career path strategy on healthcare performance and explain the factors influencing their performance. This study is an analytic quantitative study with a cross-sectional design conducted at Palmatak Regional Hospital, Kepulauan Anambas Regency. The population of this study is all healthcare workers in Palmatak Regional Hospital, amounting to 140 healthcare workers, and all population included as sample (total sampling). The data in this study was collected using a questionnaire whose validity and reliability had been tested. This study finds that work hours, training, career development, and promotion significantly affected healthcare workers' performance (p<0.05). Amongst them, career development (OR=35.51) and training (OR=55.37) are the most influential factors in healthcare workers' job performance. This study suggested that career path, especially the presence of training and career development, positively impact healthcare workers' performance. This study also encourages hospital management to regularly hold training and encourage their workers to develop themselves.Keywords: Career path, healthcare workers, performance, hospital.